2013
DOI: 10.1016/j.ejphar.2012.11.027
|View full text |Cite
|
Sign up to set email alerts
|

NAAG peptidase inhibitors and deletion of NAAG peptidase gene enhance memory in novel object recognition test

Abstract: The peptide neurotransmitter N-acetylaspartylglutamate (NAAG) is inactivated by the extracellular enzyme glutamate carboxypeptidase II. Inhibitors of this enzyme reverse dizocilpine (MK-801)-induced impairment of short-term memory in the novel object recognition test. The objective of this study was to test the hypothesis that NAAG peptidase inhibition enhances the long-term (24 hr delay) memory of C57BL mice in this test. These mice and mice in which glutamate carboxypeptidase II had been knocked out were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 60 publications
2
34
1
Order By: Relevance
“…The glial enzyme, glutamate caboxypeptidase II (GCPII), converts NAAG into N -acetylaspartate (NAA) and glutamate, which gets transported into glial cells [ 206 ]. GCPII inhibitors increase the extracellular concentration of NAAG and the drugs that increase the NAAG levels are pro-cognitive in object recognition test [ 207 ]. Treatment with GCPII inhibitors, ZJ43 ( N -[[[(1S)-1-Carboxy-3-methylbutyl]amino]carbonyl]-L-glutamic acid) and 2-(phosphonomethyl) pentanedioic acid (2-PMPA) improved cognition in mice.…”
Section: Glutamatergic Systemmentioning
confidence: 99%
“…The glial enzyme, glutamate caboxypeptidase II (GCPII), converts NAAG into N -acetylaspartate (NAA) and glutamate, which gets transported into glial cells [ 206 ]. GCPII inhibitors increase the extracellular concentration of NAAG and the drugs that increase the NAAG levels are pro-cognitive in object recognition test [ 207 ]. Treatment with GCPII inhibitors, ZJ43 ( N -[[[(1S)-1-Carboxy-3-methylbutyl]amino]carbonyl]-L-glutamic acid) and 2-(phosphonomethyl) pentanedioic acid (2-PMPA) improved cognition in mice.…”
Section: Glutamatergic Systemmentioning
confidence: 99%
“…However, accumulating evidence suggested that excessive glutamate transmission induced neuron damage, and implicated in neurological disorders, such as ischemia stroke. 4 Inhibition of GCPII has been shown to attenuate excitotoxicity associated with enhanced glutamate transmission under pathological conditions. Modulation of GCPII activity with smallmolecule inhibitors has implications for the therapy of cancer 5 and inflammatory pain 6 or neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, small molecule inhibitors of GCP-II have been demonstrated to be efficacious in multiple preclinical models wherein excess glutamate transmission is implicated including traumatic spinal cord and brain injury [ 10 12 ] stroke [ 4 ], neuropathic and inflammatory pain [ 13 27 ], ALS [ 28 ], schizophrenia [ 29 ], neuropathy [ 30 , 31 ], drug abuse [ 32 35 ] and cognition [ 36 ]. In addition, GCP-II knockout animals have shown to be protected against ischemic brain injury, peripheral neuropathy [ 37 ], and have demonstrated long term memory enhancing effects [ 38 ].…”
Section: Introductionmentioning
confidence: 99%